Extracting the Single-Dispersion Fractional Cole–Cole Bioimpedance Model Based on Low-Pass Filter Technique - Pipat Prommee; Jirat Chimnoy; Natapong Wongprommoon; Khunanon Karawanich (IEEE Transactions on Instrumentation and Measurement, 2025)
This paper presents a simple approach to extracting the parameters of the single-dispersion Cole-Cole bioimpedance model. The main advantage of the proposed technique is that it is low-cost but accurate in identifying the bioimpedance models. The Cole-Cole model is simplified as a fractional low-pass filter (LPF) using a few electronic components. Based on a low-component count, the circuit can be realized using only a single operational amplifier (OPAMP), two resistors, and two potentiometers (POTs). The proposed technique can achieve a minimal error compared to the theory, ensuring accuracy. The Cole-Cole model parameter values can be extracted by measuring the filter magnitude and phase responses. The LPF topology inherently provides a low-noise output signal. Experimental results using different fruits are carried out to verify the method and compared with measurements from a commercial impedance analyzer to confirm the accuracy of the results, with the maximum errors of R0, R∞, α, and Cα being 0.94%, 2.41%, 0.85%, and 1.52%, respectively. The proposed new efficient technique provides excellent results in extracting the Cole-Cole parameters and agrees with the theoretical expectations.
Keywords: Electrical and Bioimpedance Tomography; Body Composition Measurement Techniques; Microfluidic and Bio-sensing Technologies